Remission trajectories and cognitive function in hospitalized youth with depressive episodes - Yang, Jie; Li, Nanxi; Zhu, Xuequan; Zhang, Ziheng; Chang, Sijia; Zhang, Yinbing; Gong, Haochu; Dong, Ming; Wang, Haibo; Cai, Longjun; Wang, Xiaoyi; Wang, Gang (Frontiers in Psychiatry, 2025)
BackgroundDepressive episodes in adolescents and young adults are a significant global health concern, marked by high prevalence, cognitive impairments, and elevated suicide risk. Despite their clinical importance, remission trajectories and cognitive function in hospitalized youth remain understudied, particularly in transdiagnostic contexts.MethodsThis retrospective cohort study analyzed electronic health records from 792 hospitalized patients (aged 13–22) with depressive episodes, using the Hamilton Depression Rating Scale (HDRS-17) and the Primary Cognitive Ability Test (PCAT III) to assess symptom trajectories and cognitive function. Gaussian Mixture Models identified distinct remission patterns, while linear mixed-effects models evaluated associations between depression severity, cognitive domains, and clinical factors.ResultsThree trajectory groups emerged: Severe-Rapid Remission (7.7%), Moderate-Rapid Remission (15.3%), and Moderate-Slow Remission (77.0%). Working memory was related to depression severity, and anxiety symptoms were associated with cognitive performance. Additionally, patients diagnosed with bipolar depression showed reduced performance in both language comprehension and working memory at baseline. Intensive treatments (e.g., electroconvulsive therapy) showed efficacy but highlighted variability in response.ConclusionThe findings suggest that tailored interventions addressing baseline severity, anxiety, and cognitive support may be beneficial in hospitalized youth, with possible diagnostic relevance for bipolar depression.